The Influence of Leadership, Communication and Work Discipline on Employee Performance at UMKM Bumbu Machmudah Sidoarjo - Mashudi Mashudi (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2021)
In this study aims to determine the effect of leadership, communication and work disicpline in simultan and partial to employee performannce UMKM Bumbu Machmudah, and to determined the effect of the most significant among leadhership, communication and work disicpline on employee performannce UMKM Bumbu Machmudah Sidoarjo. The result of this study took a sample of 150 employees with technique jenuh sampling and non probability sampling in UMKM Bumbu Machmudah Sidoarjo. Moreover, this study is conducted using a quantitave method, survey, explanatory reserch As well as using analysis multiple linear with SPSS version 17 for Windows. The result of this study based on Simultaneous test shows that communication and disicpline affect the employee performannce simultaneously, and partial test shows that leadership, communication and work disicpline and affect the employee performannce in UMKM Bumbu Machmudah Sidoarjo. Work disicpline show the most significant effect toward the employee performannce because it has the significance of the smallest compared with the other independent variables.